Should Developing Countries Include Article 7 in Their Tax Treaties? - Rocha, Sergio André (Revista de Direito Tributário Internacional Atual, 2017)
This article analyses if and how the article 7 of the OECD and UN Model Conventions, which deals with the taxation of Business Profits, fits into the international tax policy of developing countries.